The Prohibition of Fair Treatment Toward Perpetrators of Annexation: A Thematic-Phenomenological Analysis of Surah al-Mumtaḥanah Verses 8–9 and MUI Fatwa No. 83 of 2023 - Fatichatus Sadiyah; Moh Fauzan Fathollah (Refleksi: Jurnal Kajian Agama dan Filsafat, 2025)
This article explores the interpretation of Surah al-Mumtaḥanah verses 8–9 and its relevance to the Indonesian Ulama Council’s (MUI) Fatwa No. 83 of 2023, within the context of Israel’s ongoing annexation and aggression against Palestine. The significance of this study lies in the close thematic connection between these Qur’anic verses and the current plight of Palestinians—despite the verses not being explicitly cited in the fatwa. Employing a qualitative library research method, this article combines thematic tafsir with Alfred Schutz’s phenomenological framework to examine the meanings and implications of the verses. The analysis reveals that the verses instruct Muslims not to extend fairness or form alliances with those who expel them from their land. When contextualized within the Israeli-Palestinian conflict, the verses imply that Muslims should avoid conciliatory relations with Israel. Phenomenologically, the "because motive" behind the interpretation is Israel’s continued aggression, while the "in-order-to motive" is to support the cessation of violence and the attainment of Palestinian independence. These findings highlight the ethical and political dimensions of scriptural interpretation in response to contemporary geopolitical crises.